Place and Child Health : The Interaction of Population Density and Sanitation in Developing Countries - Hathi, Payal; Haque, Sabrina; Pant, Lovey; Coffey, Diane; Spears, Dean (World Bank Group, Washington, DC, 2014)
A long literature in demography debates the importance of place for health. This paper assesses whether the importance of dense settlement for child mortality and child height is moderated by exposure to local sanitation behavior. Is open defecation, without a toilet or latrine, worse for infant mortality and child height where population density is greater? Is poor sanitation an important mechanism by which population density in?uences health outcomes? The paper uses newly assembled data sets to present two complementary analyses, which represent di?erent points in a trade-o? between external and internal validity. The first analysis concentrates on external validity by studying infant mortality and child height in a large, international child-level data set of 172 Demographic and Health Surveys, matched to census population density data for 1,800 subnational regions. The second analysis concentrates on internal validity by studying child height in Bangladeshi districts, with a new data set constructed with Geographic Information System techniques, and controls for ?xed e?ects at a high level of geographic resolution. The paper ?nds a statistically robust and quantitatively comparable interaction between sanitation and population density with both approaches: open defecation externalities are more important for child health outcomes where people live more closely together.